Nilai Moral dalam Cerpen Kaki Palsu Maya Karya Nurul Husniyah dan Implementasi pada Pembelajaran Sastra di Sekolah Dasar - Dea Octaviani; Khaerunnisa Khaerunnisa (Institut Agama Islam Negeri Curup, 2021)
Moral values are very influential in the world of socializing in society. Moral becomes an assessment of someone to find out their behavior, including in the education field. This study aims to explain moral values contained in the short story by Nurul Husniyah entitled Maya prosthetic feet and its implementation in literature learning in elementary schools. The method used was descriptive qualitative method. Collecting data was conducted by employing library research techniques by determining the object of research, presenting data, analyzing, compiling, and drawing conclusions from the analysis of moral values and their implementation. The results of the analysis show that there are several moral values contained in this short story to be implemented in elementary schools. Based on the results of the study, it can be concluded that there are moral values, such as the value of never giving up, mutual respect, sympathy, self-confidence, and independence. Implementation in elementary schools can be done by doing something different from activities that are usually implemented in schools, such as language month activities and watching theater